PELAKSANAAN PEMBELAJARAN PENJAS ADAPTIF TERHADAP ABK TUNAGRAHITA DI SLB-N KUANTAN SINGINGI SELAMA MASA PANDEMI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was motivated by the learning of mentally retarded children during the pandemic, in which learning methods during this pandemic underwent various changes and for mentally retarded children in the learning process using special service methods including adaptive physical education. So that researchers want to know how the implementation of adaptive physical education learning for mentally retarded children at SLB-N Kuantan Singingi during the pandemic. The purpose of this study was to find out how the implementation of adaptive physical education learning for mentally retarded children during the pandemic at SLB-N Kuantan Singingi. This research is a qualitative research. The population in this study were students of special school with mental retardation and the samples in this study were school principals, adaptive physical education teachers, mentally retarded class teachers and 10 parents/guardians of mentally retarded students by collecting data through observation, interviews, and documentation. Data analysis used data reduction, data display, and conclusion drawing/verification by testing the validity of the data through source triagulation and method triagulation. The results of this study are during the pandemic the implementation of adaptive physical education learning at SLB-N Kuantan Singingi has applied distance learning methods/online, Semi-online/Offline, PTMT. The pandemic has not been implemented effectively because not all mentally retarded students can carry out adaptive physical education learning during the pandemic.Key Words: Implementation of learning, adaptive physical education, mental retardation